(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents the psychological views of medieval Eastern scholars, their initial experiences on the moral qualities of the human personality, moral maturity, intelligence, thinking, and emotional states.